Highlights of Spanish Astrophysics IV Proceedings of the Seventh Scientific Meeting of the Spanish Astronomical Society (SEA) held in Barcelona, Spain, September 12-15, 2006 - Figueras, Francesca; Girart, Josep Miquel; Hernanz, Margarita; Jordi, Carme; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
This volume documents the contributions presented at the Seventh Scientific Meeting of the Spanish Astronomical Society (Sociedad Española de Astronomía, SEA). The event bought together 301 participants who presented 161 contributed talks and 120 posters, the greatest numbers up to now. The fact that most exciting items of the current astronomical research were addressed in the meeting proofs the good health of the SEA, a consolidated organization founded fifteen years ago in Barcelona. Two plenary sessions of the meeting were devoted to the approved entrance of Spain as a full member of the European Southern Observatory (ESO) and to the imminent first light of the greatest telescope in the world, the GTC (Gran Telescopio de Canarias), milestones that will certainly lead the Spanish Astronomy in the next future.
Spain in ESO -- Youth, Accretion, and Mass Loss at the End of the Main Sequence -- The European Extremely Large Telescope -- Gamma Ray Bursts: Lighthouses of the Universe -- The VIMOS VLT Deep Survey (VVDS) -- Science with GTC -- Galaxy Surveys in the Era of Large Ground-Based Observatories -- The GTC 10 m Telescope: Getting Ready for First Light -- OSIRIS: Status and Science -- EMIR, the GTC NIR Multiobject Imager-Spectrograph -- CanariCam: Instrument Status and Frontier Science -- S.E.A. prizes -- Radiative Transfer in Molecular Lines. Astrophysical Applications -- The Star Formation History of Early-type Galaxies as a Function of Environment -- Galaxies and cosmology -- Galaxy Evolution in Galaxy Clusters: Diffuse Light in the Virgo Cluster -- The Quest for Obscured AGN at Cosmological Distances: Infrared Power-Law Galaxies -- AMIGA: A New Model of Galaxy Formation and Evolution -- The Innermost Regions of Active Galactic Nuclei – From Radio to X-rays -- Gaussian Analysis of the CMB with the Smooth Tests of Goodness of Fit -- Dark Matter in Galaxy Clusters -- Cosmology with the Largest Scale Structures: Probing Dark Energy -- Observational Cosmology at High Redshift -- An Ha Approach to the Evolution of the Galaxy Population of the Universe -- The Galaxy and its components -- Multi-Wavelength Astronomy and the Unidentified ?-ray Sources -- The Disc and Plane of the Milky Way in the Near Infrared -- AGB Stars: Nucleosynthesis and Open Problems -- Studying Galaxy Formation and Evolution from Local Group Galaxies -- Gaia: A Major Step in the Knowledge of Our Galaxy -- Cepheus A, a Laboratory for Testing and Opening New Theories on High-mass Star Formation -- The Sun and planetary systems -- A Look into the Guts of Sunspots -- Earth-like Exoplanets. Darwin: Stellar Targets and Precursor Science -- How the Comet 9P/Tempel 1 has Behaved Before, During, and After the Deep Impact Event -- Heliospheric Energetic Particle Variability Over the Solar Cycle -- Two Years of Saturn's Exploration by the Cassini Spacecraft: Atmospheric Studies -- A New Way for Exploring Solar and Stellar Magnetic Fields -- Observatories and instrumentation -- The MAGIC Telescopes (and Beyond...) -- Present and Future of Astronomy at the Observatorio del Teide -- Prospects for the William Herschel Telescope -- VO Science. The Spanish Virtual Observatory.
Keywords: Space sciences; Astronomy; Astrophysics; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astronomy, Astrophysics and Cosmology; Astrophysics and Astroparticles